(untitled) (Research, Society and Development, 2020)
The objective of this case report is to relate a malformation in a newborn male girolando breed bovine calf. The bovine presented craniofacial duplication and was sent to the Animal Diagnosis Center (CDA) at the Federal University of Rondônia (UNIR). The descriptive study of the main anatomical changes observed during the desiccation of the facial muscles and removal of the brain was performed. The anatomical parts were exposed on a board for photo documentation and description of the malformations. The diagnosis of incomplete diprosopia was made by observing the congenital lesions on the face and brain characterized through the craniofacial junction without total head separation; the animal presented triophthalmia, duplication of nasal and oral structures with lateral deviance of the right jaw side. The animal’s cerebellum was found in the opposite position and was united with the two brains through the cerebral peduncles in a caudal cranial orientation. In this case report, it was not possible to determine the malformation etiology, however, it emphasizes the importance of diprosopia in bovine and it suggests the need of further studies about the mechanism that produce cranial alterations.